Mechanizmy interkulturowych zdarzeń komunikacyjnych, w których dochodzi do zagrożenia twarzy - Grażyna Zarzycka (Postscriptum Polonistyczne)
The paper presents a fragment of the author’s research into interferences in intercultural communication with the participation of foreign students learning Polish. The research made it possible to record various stressful situations and stressogenic factors, including “face-threatening” ones, namely those involving the risk of losing one’s face, to which the foreign interlocutor, or sometimes also the other participant of the communication act, were exposed. The aim of the research is to detect mechanisms causing the image of the interlocutor or interlocutors to be upset (undermined). It also identifies and discusses didactic and non-didactic situations causing negative emotional perceptions and mental states at least in one of the communicating parties. The paper uses the concepts of “face” by E. Goffman, P. Brown and Levinson, as well as conceptual apparatus and research methodology of American communication ethnographers.